Platinum drugs-related safety profile: The latest five-year analysis from FDA adverse event reporting system data - Feng, Guowen; Zhou, Xiaodan; Chen, Jia; Li, Dan; Chen, Li (Frontiers in Oncology, 2023)
With the widespread application of platinum drugs in antitumor therapy, the incidence of platinum drug adverse events (ADEs) is always severe and high.According to the investigation, the literature was rarely reported based on the FAERS database. The ADEs related to platinum drugs remain unclear in the real world. This study aimed to explore the adverse event signals of Cisplatin, Carboplatin and Oxaliplatin, three widely used platinum-containing drugs, and to provide a reference for rational individualized clinical drug use.